(untitled) (UNED Research Journal, 2022)
Introduction: Despite having a rich and diverse native freshwater fish fauna, exotic species have been introduced to Panama since the 20th century. Objective: To report its presence in the fresh waters of Panama of a newly recorded exotic fish. Methods: Specimens were caught with gillnet in Gatun lake, on September 30, 2017. Results: Three specimens with average standard length and weight of 233mm and 307g, respectively, were identified as Pterygoplichthys disjunctivus x pardalis. This armored catfish, native to the Amazon basin, is breeding in Gatun and may threaten local species. Conclusion: The exotic fish Pterygoplichthys disjunctivus x pardalis has a reproductive population in Gatun Lake, Panama.